Extracorporeal Blood Purification Treatments for Refractory Septic Shock Following Surgery - Eun Young Kim (Journal of Acute Care Surgery)
Advancements in perioperative management and surgical techniques have led to an increased frequency of complex surgical procedures and emergency operations, particularly among elderly, and high-risk patients. Consequently, the incidence of severe complications such as intra-abdominal infections has risen, and in some cases, there is progression to refractory septic shock, a life-threatening condition unresponsive to typically effective source control and intensive treatments. Extracorporeal blood purification therapies, including CytoSorb, polymyxin B hemoperfusion (PMX-HP), and AN69-Oxiris, have emerged as adjunctive treatments for refractory septic shock. They remove excessive cytokines and circulating endotoxins, mitigating immune dysregulation, and improving outcomes. CytoSorb filters primarily remove cytokines based on molecular weight, whereas PMX-HP filters remove endotoxin. AN69-Oxiris combines cytokine and endotoxin removal with renal support functionality. Despite their promise, these modalities exhibit limitations such as cost considerations and variability in efficacy. PMX-HP demonstrates superior endotoxin clearance, making it preferable for severe endotoxemia, while AN69-Oxiris offers cost-effective solutions for mild endotoxemia, particularly in patients requiring renal replacement therapy. However, the absence of standardized protocols, and limited direct comparisons hinders widespread adoption. Evidence-based criteria and tailored strategies are essential to optimize the clinical application of blood purification therapies, and improve outcomes for patients with refractory septic shock.